Long term reshaping of language, sensory, and motor maps after glioma resection: a new parameter to integrate in the surgical strategy. Issue 4 (1st April 2002) - Duffau, H; Denvil, D; Capelle, L
Abstract : Objectives: To describe cortical reorganisation and the effects of glioma infiltration on local brain function in three patients who underwent two operations 12–24 months apart. Methods: Three patients who had no neurological deficit underwent two operations for low grade glioma, located in functionally important brain regions. During each operation, local brain function was characterised by electrical mapping and awake craniotomy. Results: Language or sensorimotor areas had been invaded by the tumour at the time of the first operation, leading to incomplete glioma removal in all cases. Because of a tumour recurrence, the patients were reoperated on between 12 and 24 months later. Functional reorganisation of the language, sensory, and motor maps was detected by electrical stimulation of the brain, and this allowed total glioma removal without neurological sequelae. Conclusions: These findings show that surgical resection of a glioma can lead to functional reorganisation in the peritumorous and infiltrated brain. It may be that this reorganisation is directly or indirectly caused by the surgical procedure. If this hypothesis is confirmed by other studies, the use of such brain plasticity potential could be used when planning surgical options in some patients with low grade glioma. Such a strategy could extend the limits of tumour resection in gliomas involving eloquent brain areas without causing permanent morbidity.